Faktor yang Berhubungan dengan Pemberian Imunisasi HB 0 pada Bayi Baru Lahir di Puskesmas Kereng Bangkirai: Factors Related to the Provision of HB 0 Immunization in Newborn Babies at Kereng Bangkirai Puskesmas - Dewi Safitri; Fitriani Ningsih; Riska Ovany (Jurnal Surya Medika (JSM), 2023)
The prevalence of Hepatitis B in Indonesia is caused by delays in providing immunizations. There are still many cases of hepatitis B transmission from the parturient to the baby being the main cause. The administration of the hepatitis B vaccine is useful for preventing the hepatitis B virus, which can attack and damage the liver. If this continues to happen until the child grows up, it will cause liver cancer. The purpose of this study was to determine the factors related to the provision of HB 0 immunization in newborns at the Kereng Bangkirai Health Center. The design of this study uses an analytical descriptive method with a cross sectional approach. The population in this study was all mothers who had babies aged 1-12 months in the work area of the Kereng Bangkirai Health Center. The sample in this study was some mothers who had babies 0-12 months as many as 97 babies, with a sampling technique using Purposive sampling. The data of this study were taken using a questionnaire After tabulating the existing data was analyzed using the Chi Square analysis test. The results showed that there was a relationship between knowledge (p value = 0.000<a 0.05), education (p value = 0.003<a 0.05), Family support (p value = 0.043<a 0.05). Against the provision of HB 0 immunization to newborns at the Kereng Bangkirai Health Center. The conclusion of this study is that there is a relationship between Knowledge, Education, and Family Support with the provision of HB 0 immunization to newborns at the Kereng Bangkirai Health Center. Further suggestions to improve health promotion to mothers who have babies, especially newborns and can provide health information or knowledge about the importance of HB 0 immunization in newborns regarding vaccine side effects.